Characteristics of a ’common good building’ Church of England Church: A case study in a UK southern coastal town - Terry, Ian (Ecclesial Futures, 2024)
This paper investigates the question, What does a ‘common good building’ church, that partners with others to serve homeless people, look like? This investigation will assist church leaders in focusing resources and training on an outworking of the Missio Dei that aspires to common good building. The method employed for this investigation was to produce a Qualitative Grounded Theory which tested data from focus groups against theoretical sensitising and further tested it in a ‘common good building’ conference and in abductive reflection with a range of theologians. The research outcome emphasises the significance of respectful listening in empowering, particularly those with subjugated knowledge of themselves. Further conversations are needed between understandings of mission and those of work. How power is used and abused is critical; subsidiarity is central to mission.